Correlation between Occupation, Stress Level and Breast Milk Production during Covid-19 Pandemic in Indonesia - R.Khairiyatul Afiyah; Chatarina Umbul Wahyuni; Budi Prasetyo; Muhammad Bagus Qomaruddin; Imamatul Faizah; RatnaYunita Sari; Umdatus Soleha (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Burdensand types of occupation will cause psychological stress during Covid-19 pandemic,especially jobs in the medical field. The rapid transmission of the disease and the increasing number ofpeople infected by Covid-19 bring anxiety and worry and decrease the level of happiness that will obstructthe secretion of oxytocin hormone that brings problems to breast milk production and breastfeeding process.This study was aimed at analyzing the correlation between occupation, stress level and breast milk productionduring Covid-19 pandemic in Indonesia.Method: This correlational study was conducted by using cross sectional design.Thetechniqueused to collectthe samples totaling 110 breastfeeding mothers was simple random sampling technique. The independentvariables were occupation and stress level, whereas the dependent variable was breast milk production. Thisstudy used Perceived Stress Scale (PSS) questionnaire to measure the stress level and another questionnaireto measure the smoothness of breast milk production. Furthermore, data analysis was done by using Chisquarestatistic test with the significance level of p < 0.05.Result: The result of this study showed that of 110 respondents, most of them (67%) worked in the medicalfield; nearly all (70.9%) experienced severe stress; and nearly all (80%) had unsmooth production of breastmilk. Whilst, the result of Chi-square test showed that the value of p =0.000 showing that there was acorrelation between occupation, stress level and breast milk production during Covid-19 pandemic inIndonesia.Conclusion: Occupation, stress level and breast milk production are correlated during Covid-19 pandemicin Indonesia. Therefore, the medical workers, especially nurses are expected to play their active roles toeducate and teach the breastfeeding mothers how to manage stress correctly to maintain the production ofbreast milk in any conditions.